Atividade antimicrobiana do cobre aplicado em bandejas de eclosão de incubatórios avícolas - Depner, Ronise Faria Rohde (2017)
Hatchery management and sanitation are essential to supply healthy chicks to meet the demands of the growing market, and one of the most important points in this process is the hatchery. Poor hygiene in the hatchery results in an increase in the number of contaminated eggs and chicks, which reduces hatch rates and increase mortality. Therefore proper disinfecting techniques and agents should be carried out with attention. The most common disinfectant used in the poultry industry is liquid formalin. However, several countries have restricted the use formalin so alternative disinfectants are required. Previous research has demonstrated that copper has antimicrobial properties. Studies demonstrate that under conditions of exposure to dry, copper has antimicrobial efficacy in a few minutes and when on wet surfaces in a few hours. The objectives of this thesis were: to review the antimicrobial properties of copper and their mechanisms of action and to evaluate the possibility of introducing such surfaces in veterinary medicine; to evaluate its ability to inactivate microorganisms (bacteria and fungi) present in commercial hatcheries; develop hatching baskets with antimicrobial properties by the use of copper; evaluate antimicrobial functionality and efficacy trays in commercial hatcheries. In view of the various antibacterial, antifungal and antiviral properties found, it is possible to infer the amount of benefits that copper must bring to veterinary medicine, both in animal production and in food safety and public health. Based on the results obtained, it was demonstrated the antimicrobial activity of copper against microorganisms existing in hatchery broiler environments. The copper plates were able to eliminate in the laboratory almost all contamination of their surface (105 Mesophilic Colony Forming Units and mold/yeast) in just 24 hours. The prototypes produced were considered adequate, because they fitted perfectly in the plastic trays and resisted cleaning procedures without causing locomotion problems to the chicks and no adverse effects were observed. When comparing only the treatments with the basket cast, the average counts of mesophilic, Escherichia coli and molds and yeasts reduced in contact with the copper. Future studies are required to determine the optimal prototype of the delivery basket and make it a commercial product.